ANALISA DAYA DUKUNG PONDASI TIANG PANCANG PADA PROYEK PEMBANGUNAN GEDUNG ARSIP DINAS BINA MARGA PROVINSI DKI JAKARTA - Allamah Kamil; Fatmawati Oemar (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2023)
The foundation is the structure of the lower part of the building that is directly related to the ground and a part of the construction that functions to withstand the load on it. In order to improve public services in the field of infrastructure development, the Dinas Bina Marga Provinsi DKI Jakarta according to its main duties and functions, it is necessary to be supported by adequate facilities and infrastructure. The Bina Marga Service Archive Building functions as archive storage, so a safe and sturdy building is needed in accordance with existing technical provisions. In this study, we will describe the analysis of internal load carrying capacity with the N-SPT formula from Meyerhof. Calculated with Microsoft Excel and SAP2000 programs. Based on the results of the laboratory calculation above, the foundation design will be known based on soil investigation data in the field and also the calculation of the soil carrying capacity analysis formula. From the results of the analysis of the calculation of the bearing capacity of the pile with a pile size of 25 x 25 cm, based on laboratory data, the value of Qu = 103,209 tons, the value of the pile group bearing capacity is Qg = 240,821 tons and the number of piles is 7, while from the N-SPT data, the value of Qu = 186.00 tons, Qg = 301.0 tons and the number of poles is 5 pieces. So that arrangement of foundation is consider safe to use.